An acceptance towards e-Cafe system among UiTM students / Azico Abdu Rahim - Abdu Rahim, Azico (2006)
e-Cafe refers to the electronic cafeteria as it's defines as a type of restaurant in which the customers serve themselves or are served at a counter and take the food to the tables to eat by providing a selection of food from which a choice may be made and commerce conducted electronically which is payment via debit payment. In UiTM environment, e-Cafe is defining as student food subsidy electronic system that fully financial support by Malaysian government. This research seeks to determine the student's acceptance towards e-Cafe system and to determine the level of student's satisfaction towards e-Cafe system. This research use Extended Technology Acceptance Model in determine the student's acceptance towards e-Cafe system. Primary data were collected through design questionnaires that based on Extended Technology Acceptance Model. 500 students who use e-Cafe was randomly selected at UiTM main campus which including Colleges of Teratai, Meranti, Jati, Mawar and Delima in order to participating in this survey. From 500 sets of questionnaires only 472 set questionnaires were obtain back. Pearson correlation coefficient was performed on the data. The Crosstabs analysis was also performed to take the results of Pearson chi-square test to identify the relationship between variable and prove hypotheses. The measurement of the level of satisfaction is calculated based on the range scale from 5 Likert scale that are based on the modified Minnesota Satisfaction Questionnaire (MSQ) version 1977. Correlation coefficient analyses result shows there is significant relationship between perceived usefulness (PU), perceived ease of use (PEOU), attitude toward use (ATU) and behavioral intention to use (BITU). Crosstabulation analysis indicates that only student's residential status is not significant with satisfaction (S). In determination of level of student's satisfaction towards e-Cafe system, calculated statistical mean shows that respondent are neither dissatisfied nor satisfied towards e-cafe system. There are some limitations in this research and some recommendations are identified in order to overcome the limitations. This study can be extended to different type of respondents.